Development of a Software Procedure for Curved Layered Fused Deposition Modelling (CLFDM) - Huang, Bin (Auckland University of Technology, 2009)
Fused Deposition Modelling (FDM) is one of the most widely used Rapid Prototyping processes that uses the technique of depositing a semi-solid material in layers to build up a part and finds application in a variety of situations, be it making a mould for the rapid production of an industrial tool or the production of models for preoperative planning of complex cranial reconstructive surgery. When it comes to directly producing the end products, the process is still in its infancy, using inferior materials and flat layer deposition, bringing forth shortcomings such as poor surface quality, low strength for curved parts, and undesirably higher number of layers. Some of these shortcomings can be overcome if material deposition is modelled in curved layers as against the traditional flat-layer slicing and deposition. While the stair case effect can be significantly minimized, mechanical properties of the parts will also be enhanced due to continuity in fibres and the elimination of the inherent weakness between laminations. However, this being a fairly new idea, there are no existing facilities for practically implementing and experimentally testing this concept of Curved Layered Fused Deposition Modeling (CLFDM). The current research is to develop both hardware and software systems to build a working FDM system and implement CLFDM. The project involves the construction of an FDM system and then development of mathematical models for curved slicing. The numerical data generated from curved slicing algorithms is integrated with the hardware system for the practical implementation of CLFDM. Efficient curved slicing algorithms are developed and successfully used on the FDM system built for the practical implementation of CLFDM. Several case studies involving geometrical complications of increasing complexities have been successfully modelled and physically produced using CLFDM.
Keywords: Curved Layered Fused Deposition Modelling; CLFDM; Rapid prototyping